Effectiveness of small-sided games on change of direction speed in youth soccer players: a systematic review and meta-analysis - Neag, Ioan; Mihaila, Ion; Fleancu, Leonard Julien; Acsinte, Alexandru; Popescu, Corina Daniela; Stancu, Maura; Potop, Vladimir; Trandafirescu, Gabriel; Mihai, Ilie (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Purpose. Football requires both linear movements and directional changes, crucial for performance. This systematic review and meta-analysis evaluate small-sided games (SSGs) versus other training methods for enhancing change of direction speed in young soccer players.Methods. Following PRISMA guidelines, studies were sourced from Web of Science, PubMed, and Scopus. Inclusion criteria: healthy soccer players aged 6–19, SSG training programs of at least 4 weeks, and a control group. Data were assessed using the PEDro scale, and a meta-analysis was conducted using Hedges’s g ES.Results. Fourteen studies were included. The analysis showed no significant differences between SSGs and running-based methods in change of direction speed (ES = –0.04, 95% CI = –0.30 to 0.21, p = 0.74). Significant improvements were ob-served within groups for both running-based methods (ES = –0.61, 95% CI = –0.89 to –0.33, p < 0.001) and SSG interventions (ES = –0.67, 95% CI = –0.91 to –0.44, p < 0.01). No significant differences were found comparing SSGs to technical skills and running-based methods due to high heterogeneity (ES = –0.84, 95% CI = –3.72 to 2.04, p = 0.568). Combined SSG interven-tions showed significant improvements (ES = –0.72, 95% CI = –1.03 to -0.41, p < 0.001).Conclusions. SSG interventions are as effective as running-based methods in improving change of direction speed among young soccer players. Combined SSG interventions with other methods demonstrated robust improvements.
Keywords: agility; training methods; youth soccer; small-sided games; change of direction speed